Skrining Fitokimia, Profil Kromatografi Lapis Tipis dan Karakterisasi FTIR Ekstrak Etanol Daun Rambutan (Nephelium lappaceum L.) - Adinda Seftia; Suprianto; Effendy De Lux Putra; Samran; Siti Nurbaya (Yayasan Penelitian dan Inovasi Sumatera, 2025)
Background: Rambutan (Nephelium lappaceum L.) leaves have potential as a source of bioactive secondary metabolites, yet baseline data on their preliminary chemical profile and functional-group features are still limited. Objective: This study aimed to (i) screen the phytochemical constituents of rambutan leaf ethanol extract, (ii) verify major metabolite classes using thin-layer chromatography (TLC), and (iii) characterize dominant functional groups by Fourier Transform Infrared (FTIR) spectroscopy. Method: Dried rambutan leaves collected from Langkat Regency and Binjai City were extracted by maceration with 96% ethanol (1:10; 3×24 h), followed by remaceration (1×24 h). The filtrate was concentrated at 58 °C. Qualitative tests were conducted for alkaloids, flavonoids, tannins, saponins, and steroids. TLC analysis employed silica gel 60 F254 plates with class-specific mobile phases, while FTIR spectra were recorded in the range of 4000–600 cm⁻¹. Results: The extract yield was 25.7%. Phytochemical screening confirmed the presence of alkaloids, flavonoids, tannins, saponins, and steroids, with TLC Rf values of 0.70 and 0.46 (alkaloids), 0.80 (flavonoids), 0.70 (tannins), and 0.50 (steroids). FTIR bands at 3365 cm⁻¹ (O–H), 3010 cm⁻¹ (aromatic C–H), 1629 cm⁻¹ (C=C), and 1048 cm⁻¹ (C–O) indicated oxygenated secondary metabolites, particularly phenolic-related compounds. Conclusion: The integrated phytochemical screening, TLC, and FTIR approach provides a concise chemical baseline for rambutan leaf ethanol extract, supporting its potential use in further standardization and marker-based studies.